Pengaruh Penggunaan Mobile Banking terhadap Kepuasan Nasabah Bank Syariah Indonesia Cabang Jambi - Abdul Gani; Putri Apria Ningsih; Ahmad Syahrizal (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to reveal the effect of using mobile banking on customer satisfaction at Bank Syariah Indonesia Jambi Branch. This thesis uses a quantitative approach using a simple partial regression statistical analysis method with a sample of 68 customers. The results of the study show that there is a significant influence on the mobile banking usage variable (X) on customer decisions. with the tcount value on the mobile banking usage variable (X) amounting to 12,944 with a significance level of 0,000. Because the value of tcount is greater than ttable (12,944 > 2,387) and a significance value of 0.00 <0.05, Ho is rejected and Ha is accepted. Then the mobile banking usage variable (X) partially has a significant influence on customer decisions in using Bank Syariah Indonesia Mobile Banking Jambi Branch.